Communication Model of Internalising Tolerance for Women in Islamic Boarding Schools - M.W Wonuola; Wina Kurnia; Muyasaroh, Siti (Communicator: Journal of Communication, 2025)
Women's empowerment is a crucial aspect of the strategic role of Islamic boarding schools, which encompasses women's contributions in education, politics, health, and the economy. This study aims to explore the dynamics of communication processes in women's empowerment at the Ngalah Islamic Boarding School in Kediri City and to formulate a communication model that captures these mechanisms. This study employs a qualitative case study approach and draws on Joseph A. Devito's communication model, which comprises the wheel, chain, circle, Y, and star models. Data was obtained through observation, in-depth interviews, and documentation of activities related to women's empowerment in the Pesantren environment. The results of the study show that the communication process used in women's empowerment in PP. Ngalah comprises three main models: the chain, wheel, and star models. The chain model is evident in the process of synchronising hierarchical information, such as in book recitation activities and routine meetings. The model is evident in the pattern of communication between the caregiver or central figure and the female students, mediated by Mauidloh Hasanah and health counselling. Meanwhile, model stars are seen in participatory and interactive communication patterns that develop in entrepreneurship training and skills programs. The combination of this third model reflects the communication strategy of Islamic boarding schools that are adaptive in empowering women holistically across the spiritual, social, and economic realms.